Dysregulated neural coding in the vagus nerve during long sepsis - Joshua J. Strohl; Tomás S. Huerta; Sergio Robbiati; Patricio T. Huerta (Brain, Behavior, & Immunity - Health, 2025)
Sepsis is a life-threatening condition characterized by organ dysfunction resulting from the body's unbalanced and excessive response to an infection. ‘Long sepsis’ (LS) is an emerging concept referring to persistent sequelae experienced by long-term sepsis survivors, which include cognitive impairment, immune dysfunction, high cardiovascular risk, fatigue, and depression. Here, we investigated the role of the vagus nerve, a key component of the inflammatory reflex, in a mouse model of LS. Six weeks after cecal ligation and puncture (CLP) or sham surgery, we performed electrophysiological recordings from the cervical vagus nerve in anesthetized male mice. We found that LS mice exhibited significantly higher baseline vagal activity compared to controls, with elevated firing rates during both respiratory bursts and inter-burst intervals. Control mice showed clear increases in vagal activity following systemic administration of pro-inflammatory cytokines, tumor necrosis factor (TNF) and interleukin-1β (IL-1β), but LS mice displayed markedly dysregulated responses. LS mice showed altered firing dynamics, with many vagal units decreasing rather than increasing their activity after cytokine stimulation. Using a naïve Bayes decoder, we demonstrated that LS disrupted the neural code in the vagus nerve, significantly altering its activity pattern in response to cytokine signals. These results suggest that LS fundamentally alters vagus nerve function, with elevated baseline activity and diminished responsiveness to inflammatory signals. This neurophysiological dysregulation may contribute to the persistent multi-organ dysfunctions observed in long sepsis survivors, suggesting a potential role for vagal signaling in sepsis outcomes.